The Peculiarities of the Methodology of Teaching Accounting by G.A. Bakhchisaraytsev — the Representative of the Moscow Accounting School - G. V. Mikhailova; E. V. Potekhina (Учёт. Анализ. Аудит, 2018)
The progressive development of accounting in both theoretical and practical terms has an extremely complex historical and evolutionary character. At the same time, domestic periods have always been characterized by periods of both the strengthening of original national principles and their weakening. Therefore, it is very important to achieve harmonization of these separate aspects of comprehension of accounting science, allowing simultaneously to take into account not only national economic interests, but also to use the best world experience. The presented article is just considering these features on the example of the scientifc and teaching creativity of one of the outstanding representatives of the Moscow accounting school, G.A. Bakhchisaraytsev. Here it is necessary to take into account a different understanding of the accounting methodology that existed at that time in Russia. The generalizations and conclusions presented in the article make it possible to ensure a holistic perception of the preparation of accounting personnel, to prove the correctness of the consistent study of thematic materials that allow accounting to be considered as an informational reﬂection of a single reproduction cycle with the access to the system of the most important fnancial and result and exchange indicators. This approach is widely used in modern methods of teaching accounting. In addition, it is necessary to note the severity of the problem of training highly professional accountants, and in this respect, referring to the experience of G.A. Bakhchisaraytsev, we should remember the need for a high degree of responsibility for training accounting personnel. It emphasizes the exceptional importance of the continuity of training in accounting, including through self-education, which allows you to expand the range of professional knowledge, and thus increase the credibility and importance of the accounting profession.